2y+3(y-2)=29

Simple and best practice solution for 2y+3(y-2)=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+3(y-2)=29 equation:


Simplifying
2y + 3(y + -2) = 29

Reorder the terms:
2y + 3(-2 + y) = 29
2y + (-2 * 3 + y * 3) = 29
2y + (-6 + 3y) = 29

Reorder the terms:
-6 + 2y + 3y = 29

Combine like terms: 2y + 3y = 5y
-6 + 5y = 29

Solving
-6 + 5y = 29

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 5y = 29 + 6

Combine like terms: -6 + 6 = 0
0 + 5y = 29 + 6
5y = 29 + 6

Combine like terms: 29 + 6 = 35
5y = 35

Divide each side by '5'.
y = 7

Simplifying
y = 7

See similar equations:

| C=240+0.75Y | | 3(x+4)=2(11-x) | | -2=6(x+3)-2x | | 284=-66a | | 4x^2+2x+1=o | | 2x-2=11-4x | | (X-5)^5/3-73=170 | | 10^6/10^2= | | n+1.2=7.4 | | Tan(28)=x/32 | | 4c-39=43c-78 | | 3(7+3x)=30 | | 5/3m=5/9 | | (q-12)(6q+1)=0 | | 150=x+1.5x | | 2/7×7/2x=424×2/7 | | -5(5y-2)-y=-2(y-3) | | 8-3x+13=15 | | 5x+3.9=3x+27 | | 20=4x-5y | | S=Y-(150+0.60Y) | | 0.0l(500-70x)=3.2x+300 | | -4m+8=-12 | | 5(3x+12)-12x= | | 5.5x+19=6.75x+9 | | 30-x=2x+3 | | 30x=12 | | 16+8x=x^2 | | t+68=7t-58 | | 4x-5+2(x-3)=12x+5 | | 6-4y=14 | | 7x-25=-63 |

Equations solver categories